Adsorption of heavy metal ions from aqueous solutions using a functional polymer adsorbent / Mohamad Izzat Arif Nordin - Nordin, Mohamad Izzat Arif (2023)
Environmental pollution caused by untreated discharge containing heavy metal is alarming due to the toxicity. Continuous efforts in producing an economical, robust, and efficient sorbent for a variety of water pollutants such as dyes, heavy metals, microorganisms are actively being pursued. In this study, a double network polymer network consisting poly(1-vinylimidazole-co-acrylic acid)/poly(vinyl alcohol) (P(VI-co-AA)/PVA adsorbent were successfully synthesized as functional polymer adsorbent via in-situ free-radical polymerization followed by cyclic freeze-thaw. P(VI-co-AA)/PVA was characterized by using NMR, FTIR, FESEM and TGA. As a double polymer network, the swelling behaviour of P(VI-co-AA)/PVA adsorbent was slower and more controlled in deionized water and phosphate buffer solution at pH 7 compared to dramatic swelling of the single polymer network, P(VI-co-AA), which showed tendency to rupture after several hours of swelling in the aqueous media. Batch adsorption of Cu2+ and Pb2+ by the P(VI-co-AA)/PVA adsorbent was conducted under ambient conditions, at pH 6 and initial metal ion concentration of 100 ppm using two different adsorbent dosages until adsorption equilibria were achieved. The metal ions adsorption efficiencies of the P(VI-co-AA)/PVA adsorbent were compared with the single polymer networks, which were P(VI-co-AA) and PVA, where were prepared through similar experimental conditions. High removal efficiencies (>90%) for both Cu2+ and Pb2+ were reported for the P(VI-co-AA)/PVA and P(VI-co-AA) adsorbents at for the 1 g/L and 2 g/L adsorbents dosages, however, the P(VI-co-AA) network ruptured due to high osmotic pressure after several hours of adsorption. The P(VI-co-AA)/PVA adsorbents recorded 98 – 100 mg/g adsorption capacities (Cu2+ and Pb2+) at 1 g/L dosage, and the adsorption capacities for these metal ions significantly reduced by ̴ 50% when the adsorbent dosage was doubled whilst maintaining the initial metal ion concentration at 100 ppm. Therefore, the P(VI-co-AA)/PVA double-network adsorbent demonstrated enhanced mechanical properties compared to the P(VI-co-AA) single-network adsorbent and high adsorption capacities for Cu2+ and Pb2+, making it as a suitable as a functional adsorbent candidate to adsorb metal ions from wastewaters.